An industrial quality control study on Vinyl Resources, Inc. - Alzona, Jose Carlos (College of Engineering, 2002)
Vinyl Resources, Inc is a 100 percent Filipino corporation engaged in the manufacture of refrigerator and freezer gaskets as well as other polyvinyl-chloride compounds. The product understudy is the gasket GC003. The production process starts with the mixing of raw material which is then formed into pellets that are extruded then cooled to form the gasket. Magnets and foam are then inserted into the gasket which is then fused and trimmed to form the gasket frame. The problems encountered were the variation of gasket length, the machine downtime, the integrity of the fusing of gaskets and Sheet surface imperfections. These problems were identified using Ishikawa diagrams, pareto diagram, and Failure Mode Effect Criticality analysis. The use of control charts showed that the process of cutting the gasket to a certain length was out of control and the process of fusing the gaskets was also out of control. It was discovered that the process of cutting the gasket though out of control was capable. This was done by using process capability analysis. The machine downtime of the pelletizing machine was reduced by preventing contamination of the raw materials. For the length variability, it was recommended that tighter specification limits be imposed; for the sheet surface imperfection, new inspection standards should be based on objective measures; for the fusing/weld problem, and an additional tensile strength test should be conducted.